Spectroscopic Studies of some Fired Clay Artifacts Recently Excavated at Tittagudi in Tamilnadu - and G. Velraj2, K. Janaki1, (Recent Research in Science and Technology, 2011)
This paper presents the preliminary results of an investigation on pottery shreds using Fourier Transform Infrared (FT-IR) spectroscopy. The analysis has lead to initial characterization of the pottery shreds collected from the archaeological site Tittagudi in Caddalore district.